2005
DOI: 10.1142/s1084946705000057
|View full text |Cite
|
Sign up to set email alerts
|

Does Rural Location Matter? The Significance of a Rural Setting for Small Businesses

Abstract: Rural settings in the United States have characteristics that present a unique context for small business, often portrayed as adverse. Studies of rural entrepreneurs and small businesses, however, frequently fail to provide data on the rural context and its potential relationship to small business, taking for granted presumed attributes and adverse effects. To develop a better understanding of a rural setting's importance, this research investigated effects of rural geo-demographic and socio-cultural features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 18 publications
1
31
0
3
Order By: Relevance
“…Ils peuvent dès lors réaliser leurs rêves d'être indépendants et créatifs quant à l'emploi puisque la campagne leur offre cette opportunité, tel qu'observé dans d'autres pays (Saleille, 2007(Saleille, , 2006Shields, 2005;Stockdale, 2006). L'importance du travail autonome dans ce groupe est donc notable, spécialement dans la région montérégienne où il touche la majorité des néo-ruraux interrogés et actifs sur le marché de l'emploi ainsi que leurs conjoint(e)s, comparativement à la moitié dans le Centre du Québec.…”
Section: Facteurs Familiauxunclassified
“…Ils peuvent dès lors réaliser leurs rêves d'être indépendants et créatifs quant à l'emploi puisque la campagne leur offre cette opportunité, tel qu'observé dans d'autres pays (Saleille, 2007(Saleille, , 2006Shields, 2005;Stockdale, 2006). L'importance du travail autonome dans ce groupe est donc notable, spécialement dans la région montérégienne où il touche la majorité des néo-ruraux interrogés et actifs sur le marché de l'emploi ainsi que leurs conjoint(e)s, comparativement à la moitié dans le Centre du Québec.…”
Section: Facteurs Familiauxunclassified
“…La littérature montre que cette localisation, de part ses caractéristiques géo-démographiques (éloignement, manques en ressources, faible densité) et socio-culturelles (interconnaissance, appartenance à une communauté, solidarités), implique des pratiques de gestion spécifiques : stratégie coopérative implicite, importance du bouche à oreille dans la communication, imbrication des réseaux sociaux et professionnels (Shields, 2005).…”
Section: …Qui S'implante En Milieu Rural…unclassified
“…The per capita household income and educational level of rural residents tend to be low in comparison to their counterparts in urban areas, and rural businesses may lack sufficient access to financing. On the other hand, Shields (2005) has found that rural entrepreneurs viewed neither resource constraints (financing, technology and transportation) nor labour issues (availability of Public Business Services Fostering Growth -Case Studies in Northern Sparsely Populated Areas skilled workers and childcare) as significant sources of adversity. Sociocultural features such as gender roles, cooperation, communication and social and business networks are closely intertwined with small business operations in rural areas (Shields, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Shields (2005) has found that rural entrepreneurs viewed neither resource constraints (financing, technology and transportation) nor labour issues (availability of Public Business Services Fostering Growth -Case Studies in Northern Sparsely Populated Areas skilled workers and childcare) as significant sources of adversity. Sociocultural features such as gender roles, cooperation, communication and social and business networks are closely intertwined with small business operations in rural areas (Shields, 2005). In addition, Boter (2005) found that SMEs located in sparsely populated areas utilise PBSs more often than in larger regions.…”
Section: Introductionmentioning
confidence: 99%